The Utilization of Different Starter and Incubation Time on Texture, Fat Content and Organoleptic Properties of Nata de Milko - Khothibul Umam Al Awwaly; Anindhita Puspadewi; Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2011)
The purposes of this study were to determine starter level and incubation time on the quality of nata de milko and to obtain an appropriate starter concentration and incubation time to produce a good nata de milko in terms of texture, fat content and organoleptic properties. The material used was nata de milko. The research method used was factorial experiment using a randomized block design with 2 factors, namely starter concentrations were 5%, 7.5% and 10% of media, and incubation times were 7,Â  9 , and 11 days. Variables observed were texture, fat content and organoleptic properties. Tunjukkan huruf latinThe results showed that gave no effect (P>0.05) between starter concentrations and incubation times on texture and fat content, and gave an effect (P<0.05) on flavour, colour, and texture (organoleptic sensory) of nata de milko. Starter concentrations and incubation times gave a highly significant difference effect (P<0.01) on taste. The highest average value of the starter concentration found in 5% with texture, fat content, and organoleptic properties were 0.21 mm/g.sec, 0.22% and fresh aroma, white colour, sweet taste and chewy texture. The average value of 9-days incubation with texture value, fat content, andÂ  organoleptic properties were 0.19 mm/g.sec, 0.12% and fresh aroma, white colour, sweet taste and chewy texture.The concentration of starter and incubation time did not show an effect on texture and fat content of nata de milko, but showed an effect on organoleptic properties. Keywords: whey, texture, fat, organoleptic, nata de milko